2021
DOI: 10.3389/fmolb.2021.726902
|View full text |Cite
|
Sign up to set email alerts
|

Probing Isoform Switching Events in Various Cancer Types: Lessons From Pan-Cancer Studies

Abstract: Alternative splicing is an essential regulatory mechanism for gene expression in mammalian cells contributing to protein, cellular, and species diversity. In cancer, alternative splicing is frequently disturbed, leading to changes in the expression of alternatively spliced protein isoforms. Advances in sequencing technologies and analysis methods led to new insights into the extent and functional impact of disturbed alternative splicing events. In this review, we give a brief overview of the molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Remarkably, overlap between the original results of Sebetyen et al and the results obtained after applying their pipeline to our dataset was also quite low; only 40 unique genes were shared between them (approximately 17% of each result in terms of unique genes). Therefore, we cautiously argue that the choice of annotation and RNA-Seq analysis strategy might in fact account for a significant portion of discrepancy between studies investigating isoform switching, something that has been suggested before [ 23 ]. However, due to the large differences between studies in terms of methodology and technical aspects, proving this statement for certain is a tough task outside of the scope of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, overlap between the original results of Sebetyen et al and the results obtained after applying their pipeline to our dataset was also quite low; only 40 unique genes were shared between them (approximately 17% of each result in terms of unique genes). Therefore, we cautiously argue that the choice of annotation and RNA-Seq analysis strategy might in fact account for a significant portion of discrepancy between studies investigating isoform switching, something that has been suggested before [ 23 ]. However, due to the large differences between studies in terms of methodology and technical aspects, proving this statement for certain is a tough task outside of the scope of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…№ 1. doi: 10.17537/2024. 19.15 30% higher rate than in normal cells [55]. Isoform switching leads to the loss of DNA sequences encoding protein domains, significant changes in amino acid sequences, alteration of protein domains, and modification of signal peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Isoform switching (AS) is a complex and highly regulated process that contributes to proteome diversity. In normal cells, isoforms play a crucial role in regulating various biological processes; however, their abnormal expression contributes to tumorigenesis [55]. There are five major types of alternative splicing events regarding splice site selection, including (exon skipping, mutually exclusive exons, intron retention, alternative 5 splice site, and alternative 3 splice site) [56].…”
Section: Discussionmentioning
confidence: 99%